Correcting Hypernatremia in Children. Issue 3 (March 2023) - Didsbury, Madeleine; See, Emily J.; Cheng, Daryl R.; Kausman, Joshua; Quinlan, Catherine
Visual Abstract: Abstract : Background: In children with hypernatremia, current clinical guidelines recommend a reduction in serum sodium of 0.5 mmol/L per hour or less to avoid complications of cerebral edema. However, no large-scale studies have been conducted in the pediatric setting to inform this recommendation. Therefore, this study aimed to report the association between the rate of correction of hypernatremia, neurological outcomes, and all-cause mortality in children. Methods: A retrospective cohort study was conducted from 2016 to 2019 at a quaternary pediatric center in Melbourne, Victoria, Australia. All children with at least one serum sodium level ≥150 mmol/L were identified through interrogation of the hospital's electronic medical record. Medical notes, neuroimaging reports, and electroencephalogram results were reviewed for evidence of seizures and/or cerebral edema. The peak serum sodium level was identified and correction rates over the first 24 hours and overall were calculated. Unadjusted and multivariable analyses were used to examine the association between the rate of sodium correction and neurological complications, the requirement for neurological investigation, and death. Results: There were 402 episodes of hypernatremia among 358 children over the 3-year study period. Of these, 179 were community-acquired and 223 developed during admission. A total of 28 patients (7%) died during admission. Mortality was higher in children with hospital-acquired hypernatremia, as was the frequency of intensive care unit admission and hospital length of stay. Rapid correction (>0.5 mmol/L per hour) occurred in 200 children and was not associated with greater neurological investigation or mortality. Length of stay was longer in children who received slow correction (<0.5 mmol/L per hour). Conclusions: Our study did not find any evidence that rapid sodium correction was associated with greater neurological investigation, cerebral edema, seizures, or mortality; however, slow correction was associated with a longer hospital length of stay.